Simultaneous Doppler Tracing of the Mitral Inflow and Annular Motion Provides a Useful Means of Evaluating Left Ventricular Diastolic Function - Choi, Jin‐Oh (Clin Cardiol, 2008)
BACKGROUND: In this study, we evaluated the feasibility and clinical usefulness of TS [Formula: see text] , the time interval between the onsets of early diastolic mitral inflow velocity (E) and mitral annular velocity (E′), obtained by simultaneously tracing E and E′, in terms of evaluating diastolic function. METHODS: By the diastolic functional status, 105 patients were allocated to abnormal relaxation, pseudonormal filling (PN), or normal diastolic function groups (n = 30, 43, and 32, respectively). The TS [Formula: see text] was measured in the same cardiac cycle by the pulsed‐wave Doppler (PWD) tracing of mitral inflow near the septal annulus with appropriate filter and gain settings. RESULTS: TS [Formula: see text] was prolonged in the PN group versus the normal group (34.1 ± 12.2 msec versus 12.1 ± 8.5 msec, p≤0.001). The area under the receiver operating characteristic curve of TS [Formula: see text] for the detection of PN was 0.91 (95% confidence interval [CI]; 0.85 ∼ 0.97, p<0.001), and 24.0 msec was determined to be the optimal cut‐off value (specificity 83.7%, sensitivity 90.3%). CONCLUSION: Simultaneous measurement of TS [Formula: see text] is feasible and clinically applicable for the grading of diastolic dysfunction (DD). Copyright © 2008 Wiley Periodicals, Inc.